2017
DOI: 10.1021/acs.chemmater.6b04287
|View full text |Cite
|
Sign up to set email alerts
|

Propeller-Shaped Acceptors for High-Performance Non-Fullerene Solar Cells: Importance of the Rigidity of Molecular Geometry

Abstract: This paper describes the synthesis and application of βTPB6 and βTPB6-C as electron acceptors for organic solar cells. Compound βTPB6 contains four covalently bonded PDIs with a BDT-Th core at the β-position. The free rotation of PDIs renders βTPB6 with varying molecular geometries. The cyclization of βTPB6 yields βTPB6-C with high rigidity of the molecular geometry and enlarged conjugated skeleton. The inverted solar cells based on βTPB6-C and PTB7-Th as the donor polymer exhibited the highest efficiency of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 36 publications
(49 reference statements)
3
63
0
Order By: Relevance
“…[21][22][23][24][25] Indacenodithiophene (IDT) and indacenodithieno [3,2-b]thiophene (IDTT) are most widely employed as the central electron-donating donor, while 3-(dicyanomethylidene)indan-1-one (IC) and its derivatives as the terminal electron-withdrawing acceptor. [21][22][23][24][25] Indacenodithiophene (IDT) and indacenodithieno [3,2-b]thiophene (IDTT) are most widely employed as the central electron-donating donor, while 3-(dicyanomethylidene)indan-1-one (IC) and its derivatives as the terminal electron-withdrawing acceptor.…”
Section: Doi: 101002/adma201707150mentioning
confidence: 99%
“…[21][22][23][24][25] Indacenodithiophene (IDT) and indacenodithieno [3,2-b]thiophene (IDTT) are most widely employed as the central electron-donating donor, while 3-(dicyanomethylidene)indan-1-one (IC) and its derivatives as the terminal electron-withdrawing acceptor. [21][22][23][24][25] Indacenodithiophene (IDT) and indacenodithieno [3,2-b]thiophene (IDTT) are most widely employed as the central electron-donating donor, while 3-(dicyanomethylidene)indan-1-one (IC) and its derivatives as the terminal electron-withdrawing acceptor.…”
Section: Doi: 101002/adma201707150mentioning
confidence: 99%
“…Furthermore, Yu and co-workersd eveloped ap ropeller-shaped PDI derivative 21 by Suzukic ouplinga nd subsequentc yclization. [23] By comparing the photovoltaic performance of 21 with the uncyclized analogue,t hey demonstrated that careful control of the molecular geometry rigidity was an effective strategy to design high-performance organic semiconducting materials.…”
Section: Perylene Diimide Dyesmentioning
confidence: 99%
“…Asian J. 2018,13,[20][21][22][23][24][25][26][27][28][29][30] www.chemasianj.org lated PDI dyes via palladium-catalyzed SiÀCb ond formation. [37] Startingf rom 5a, 37 and 38 were obtained in one-pot reactions in high yield using Pd(OAc) 2 as the catalyst, as well as PCy 3 and KOAc as the ligand and base, respectively.T hese dyes exhibited red-shifted absorption and high fluorescence quantum yields.…”
Section: Bay-region Functionalization Of Pdis Based On Tetrahalogen-smentioning
confidence: 99%
See 2 more Smart Citations